The Educational Values of Sundanese Folktales as Reading Materials for Primary Schools - Rahmawati, Evi; Rahmat Sutedi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study is motivated by the growing concerns regarding moral, character, and ethical crises among primary school students, such as the decline in responsibility, creativity, honesty, politeness, respect, and tolerance. The purpose of this research is to describe the character education values embedded in Sundanese folktales and to identify reading instructional materials for primary schools based on the analysis of the Sasakala Talaga Warna folktale collection. This study employs a descriptive method, with data collected through literature review and document analysis. The findings indicate that Sundanese folktales contain a wide range of character education values, including religiosity, honesty, tolerance, discipline, hard work, creativity, independence, democratic attitude, curiosity, national spirit, patriotism, communication, love of peace, environmental awareness, social care, and responsibility. These results demonstrate that Sundanese folktales have strong potential to be utilized as reading materials in primary school instruction.